Targeting Glutamine Metabolism Ameliorates Autoimmune Hepatitis via Inhibiting T Cell Activation and Differentiation - Yu, Qiang; Tu, Honghu; Yin, Xueyi; Peng, Chang; Dou, Chuanyun; Yang, Wenhua; Wu, Wenbiao; Guan, Xiaotong; Li, Jia; Yan, Hexin; Zang, Yi; Jiang, Haowen; et al. (Frontiers in Immunology, 2022)
Background Autoimmune hepatitis (AIH) is mediated by a cascade of T cell-mediated events directed at liver cells and persistent inflammation within the liver can eventually result in liver cirrhosis. Targeting glutamine metabolism has an impact on T cell activation and differentiation. However, the effect of glutamine metabolism blocking upon AIH remains unknown. We use glutaminase antagonist 6-diazo-5-oxo-L-norleucine (DON) for in vitro assays and its prodrug 2-(2-amino-4-methylpentanamido)-DON (JHU083) for in vivo assays to investigate the potential therapeutic effect and molecular mechanism of glutamine metabolism blocking in an AIH murine model. Methods AIH mice were treated with JHU083 or vehicle before concanavalin A (ConA) administration, and disease severity was examined. Then activation and differentiation [including Th1/Th17 cells and cytotoxic T lymphocytes (CTL)] of T cells from Vehicle-WT, JHU083-AIH and Vehicle-AIH mice were tested. Furthermore, in vitro T cell activation and differentiation were measured using separated splenocytes stimulated with ConA with or without DON. The activation and differentiation of T cells were tested using flow cytometry, qRT-PCR and ELISA. Phosphorylation level of mammalian target of rapamycin (mTOR) and 70 kDa ribosomal protein S6 kinase (P70S6K) were examined by western blotting. Results JHU083 and DON significantly suppressed the activation of T cells and inhibited the differentiation of Th1/Th17 cells and CTL in vivo and in vitro. Besides, we demonstrated that glutamine metabolism blocking inhibited T cells activation and differentiation through decreasing the mRNA expression of amino acid transporter solute carrier family 7 member 5 (SLC7A5) and mitigating the activation of mTOR signaling. Conclusions We proved that targeting glutamine metabolism represents a potential new treatment strategy for patients with AIH and other T cell-mediated disease. Mechanistically, we demonstrated that glutamine metabolism blocking inhibits T cells activation and suppresses the differentiation of Th1/Th17 cells and CTL.